Dissecting the immune evasion and therapeutic resistance mechanisms in EGFR/TP53 co-mutated non-small cell lung cancer: implications for targeted and immunotherapy strategies - Shi, Haiyan; Xu, Kun; Kong, Xueying; Xie, Weining; Chen, Yingying; He, Ding; Cheng, Zufu; Huo, Xianshan; Gao, Ke; Song, Mingshuang; Tian, Ning (Frontiers in Immunology, 2025)
BackgroundAlthough precision-targeted therapies and tyrosine kinase inhibitors (TKIs) have significantly improved outcomes in non-small-cell lung cancer (NSCLC), patients with EGFR-mutant NSCLC with concurrent TP53 mutations often develop drug resistance and experience poor clinical outcomes. This study aims to investigate the molecular mechanisms underlying this aggressive subtype using single-cell RNA sequencing.MethodsFormalin-fixed paraffin-embedded (FFPE) tumor samples were obtained from 40 hospitalized NSCLC patients. Somatic mutation profiles were determined using a targeted 23-gene next-generation sequencing (NGS) panel. Four samples harboring concurrent EGFR and TP53 mutations were selected for single-cell transcriptomic profiling using the 10x Genomics platform.ResultsTwo dominant malignant epithelial cell populations were identified: C1_EGFR+, associated with proliferation and invasion, and C2_STAT1+, linked to immunosuppression and drug resistance. These tumor subtypes cooperatively drive CD8+ T cell exhaustion through the MDK–(ITGA4+ITGB1), MIF–(CD74+CXCR4), and TGF-β signaling pathways. In addition, antigen-presenting cancer-associated fibroblasts (apCAFs) recruit regulatory T cells via the CCL5–CCR4 axis, collectively establishing an immune-excluded tumor microenvironment. Mechanistically, a STAT1/ETS1-centered transcriptional program regulates the expression of key immunosuppressive (e.g., MDK, MIF, TGFB1) and resistance-associated genes (e.g., ERBB2, JAK2).ConclusionThese findings reveal a coordinated transcriptional network that promotes immune evasion and therapeutic resistance in EGFR/TP53 co-mutated NSCLC. Targeting the STAT1/ETS1 axis, in combination with EGFR-TKIs or immune checkpoint inhibitors, may provide a novel strategy to overcome resistance and improve patient outcomes. Further validation in larger patient cohorts and functional studies is warranted to confirm these observations and support clinical translation.